Understanding Citizen Journalism from the Perspective of Young Journalists in Malaysia: Comprender el periodismo ciudadano desde la perspectiva de los periodistas jóvenes en Malasia - MAHAMED, M.; ZOBIDAH OMAR, S.; ERIC KRAUSS, S. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACTCitizen journalism is increasingly practiced worldwide due to the expansion of the Internet, new media technologies, and social media platforms. This study investigated Malaysia's citizen journalism through young journalist’s perspective by understanding the concepts and roles of citizen journalists. The analysis demonstrated that young citizen journalists view opportunities and empowerment from a new angle. The results illustrated that citizen journalism in Malaysia provides a potential prospect for citizen journalists as well as a role in inspiring young people. Based on the present paper, it is suggested that future research should explore the guidelines to distinguish Malaysian citizen journalists from the conventional keyboard warriors and cyber troopers. RESUMENEl periodismo ciudadano se practica cada vez más en todo el mundo debido a la expansión del Internet, las nuevas tecnologías de medios y las plataformas de redes sociales. Este estudio investigó el periodismo ciudadano de Malasia a través de la perspectiva de los periodistas ciudadanos jóvenes mediante la comprensión de los conceptos y roles de los mismos. El análisis demostró que los periodistas ciudadanos jóvenes ven las oportunidades y el empoderamiento desde un nuevo ángulo. El resultado ilustró que el periodismo ciudadano en Malasia ofrece una perspectiva potencial para los periodistas ciudadanos y también un papel para inspirar a los jóvenes. Con base al presente artículo, se sugiere que la investigación futura debería explorar las pautas para distinguir a los periodistas ciudadanos malasios de los guerreros del teclado y los ciberdelincuentes convencionales.